THOUSHTS ABOUT BARAKA: https://doi.org/10.5281/zenodo.14763031 - Ismoilov , Sobirjon (Journal of Contemporary World Studies, 2025)
The followins article enlightens importance and content of Baraka on the bascment of ayats, hadith, proverbs and speeches jf philosophers, also guahties, that exclude baraka.